(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
The methanolic extract of Litsea glutinosa (Lauraceae) was evaluated for in vitro antioxidant activity by determination of hydrogen peroxide scavenging activity, total antioxidant capacity, assay of nitric oxide scavenging activity and reducing power test and in vivo antinociceptive effect in acetic acid induced writhing model in swiss albino mice. The results revealed the presence of pronounced antioxidant property as compared with ascorbic acid used as standard and a dose-dependent (250 and 500 mg/kg) analgesic effect. The antioxidant and antinociceptive properties observed seem to be in good accordance with the traditional uses of Litsea glutinosa. Bangladesh J. Sci. Ind. Res. 47(4), 401-406, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.14069